(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
This study aims to develop and analyse a new weave structure for producing Double-Face Figured (DFF) reversible fabrics that overcome the limitations of existing designs. DFF fabrics, composed of two interlaced layers displaying distinct images on either side, are traditionally woven using self-stitched double cloth or four-weft orthogonal weaves. However, these methods yield coarse textures or require dual warp beams. To address these issues, a Layer-to-Layer Angular Interlock (LLAI) weave structure is proposed and evaluated for its suitability in DFF weaving. The LLAI weave is designed on a 6-end × 8-pick grid, resulting in four cloth parts formed by superimposed images. Corresponding weaves are developed for each part, with additional variations created by interchanging picks to achieve balanced lifting in a body-border style. Computer-aided design tools are used for motif creation, guide graph development, superimposing, and weave application. Fabric samples are woven using both electronic and mechanical jacquards to validate the structure. Results confirm that the LLAI weave enables the smooth interchanging of plain structures without any weave prominence and can be woven using a single warp beam. The new weave structure thus offers improved texture, design flexibility, and production efficiency, making it suitable for reversible garments, dress materials, home furnishings, carpets, and technical textiles.